2007
DOI: 10.1186/1471-2407-7-194
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of TLR3 are associated with Nasopharyngeal carcinoma risk in Cantonese population

Abstract: Background: Nasopharyngeal carcinoma is endemic in Southern China, displays a strong relationship with genetic susceptibility and associates with Epstein-Barr virus infection. Toll-like receptor 3 (TLR3) plays an important role in the antivirus response. Therefore, we examined the association between TLR3 gene polymorphisms and NPC susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 41 publications
4
43
0
2
Order By: Relevance
“…27 It is proposed that the genetic polymorphisms of TLR3 are associated with nasopharyngeal carcinoma risk. 28 Our data are in line with these previous studies by showing that the exposure to TLR3 ligands, the Poly I:C, activates NPC cells; such an activation induces the expression of miR-21 by NPC cells.…”
Section: Assessment Of the Immune Suppressor Functions Of Npcinduced supporting
confidence: 82%
“…27 It is proposed that the genetic polymorphisms of TLR3 are associated with nasopharyngeal carcinoma risk. 28 Our data are in line with these previous studies by showing that the exposure to TLR3 ligands, the Poly I:C, activates NPC cells; such an activation induces the expression of miR-21 by NPC cells.…”
Section: Assessment Of the Immune Suppressor Functions Of Npcinduced supporting
confidence: 82%
“…Stimulation of TLR3 directly induced cell apoptosis in a poly I:C-dependent manner. nasopharyngeal carcinoma (16). In this study, we clarified that HNSCCs showed varied TLR expression and that they tended to show strong TLR3 expression.…”
Section: Discussionmentioning
confidence: 86%
“…TLR3 is expressed in breast cancer (10), melanoma (11), prostate cancer (12), cervical cancer (13), colon cancer (13), hepatocellular carcinoma (14) and head and neck cancer (15), while TLR4 is expressed in lung cancer (17). In HNSCCs, studies of TLR expression have been reported by only two investigators (15,16). Pries and his colleagues reported TLR3 expression and signaling in HNSCCs (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies have investigated the association between TLRs polymorphisms and cancer risk (Zhou et al, 2006;He et al, 2007;Purdue et al, 2009;Ng et al, 2010;Monroy et al, 2011), but the results were inconclusive. Different from the similar meta-analysis in Neoplasma (Wang et al, 2013), the Delta22 polymorphism (-196 to 174 del) was not analyzed in our manuscript.…”
Section: Discussionmentioning
confidence: 99%